Analysis and Validation of Human Targets and Treatments Using a Hepatocellular Carcinoma–Immune Humanized Mouse Model. Issue 3 (15th September 2021) - Zhao, Yue; Wang, Jiaxu; Liu, Wai Nam; Fong, Shin Yie; Shuen, Timothy Wai Ho; Liu, Min; Harden, Sarah; Tan, Sue Yee; Cheng, Jia Ying; Tan, Wilson Wei Sheng; Chan, Jerry Kok Yen; Chee, Cheng Ean; et al.
Abstract : Background and Aims: Recent development of multiple treatments for human hepatocellular carcinoma (HCC) has allowed for the selection of combination therapy to enhance the effectiveness of monotherapy. Optimal selection of therapies is based on both HCC and its microenvironment. Therefore, it is critical to develop and validate preclinical animal models for testing clinical therapeutic solutions. Approach and Results: We established cell line–based or patient‐derived xenograft–based humanized‐immune‐system mouse models with subcutaneous and orthotopic HCC. Mice were injected with human‐specific antibodies (Abs) to deplete human immune cells. We analyzed the transcription profiles of HCC cells and human immune cells by using real‐time PCR and RNA sequencing. The protein level of HCC tumor cells/tissues or human immune cells was determined by using flow cytometry, western blotting, and immunohistochemistry. The HCC tumor size was measured after single, dual‐combination, and triple‐combination treatment using N‐(1ʹ, 2‐Dihydroxy‐1, 2ʹ‐binaphthalen‐4ʹ‐yl)‐4‐methoxybenzenesulfonamide (C188‐9), bevacizumab, and pembrolizumab. In this study, human immune cells in the tumor microenvironment were strongly selected and modulated by HCC, which promoted the activation of the IL‐6/Janus kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3) signaling pathway in tumor cells and led to augmented HCC proliferation and angiogenesis by releasing angiogenic cytokines in humanized‐immune‐system mice with HCC. In particular, intratumor human cluster of differentiation–positive (hCD14 + ) cells could produce IL‐33 through damage‐associated molecular pattern/Toll‐like receptor 4/activator protein 1, which up‐regulated IL‐6 in other intratumor immune cells and activated the JAK2/STAT3 pathway in HCC. Specific knockdown of the CD14 gene in human monocytes could impair IL‐33 production induced by cell lysates. Subsequently, we evaluated the in vivo anti‐HCC effect of C188‐9, bevacizumab, and pembrolizumab. The results showed that the anti‐HCC effect of triple‐combination therapy was superior to that of single or dual treatments. Conclusions: Humanized‐immune‐system HCC mouse models are suitable for identifying targets from cancer and immune components and for testing combinational therapies.